Chronostratigraphy of a loess-paleosol sequence in the western Chinese Loess Plateau based on ESR dating and magnetostratigraphy. (10th November 2022) - Niu, Yanning; Fan, Yuxin; Qiao, Yansong; Lü, Tongyan; Li, Chaozhu; Qi, Lin; Wang, Sheng; Peng, Shasha; Tan, Yuanlong
Abstract: The western area of the Chinese Loess Plateau (CLP) is close to the northeastern margin of the Tibetan Plateau (NTP) and arid regions of northern China. Loess-paleosol sequence is a good archive for studying the variation of the East Asian summer monsoon (EASM) and the evolutionary history of paleoclimate. However, excessive remagnetization makes it challenging to infer the location of the time-scaled strata, and only a few high-resolution long scale paleomagnetic data are available from the western CLP. To solve this problem, this paper presents a study on establishing a Quaternary chronological framework using the traditional paleomagnetic method and quartz electron spin resonance (ESR) dating. The result is validated by comparing sequences in a variation of magnetic susceptibility and grain-size. Detailed thermal demagnetization records show that declination is reversed, but the inclination reversal is not apparent between S7 and S8. ESR estimated that the three samples collected at a depth of ∼112–145 m were 853.51 ± 133.43 ka, 962.12 ± 144.30 ka, and 1004.27 ± 206.86 ka, respectively. Constrained by these ESR dates, the age of the L9-L15 is defined as ∼0.9–1.2 Ma, which is corroborated the observation in the field stratigraphic survey, the characteristics of magnetic susceptibility and grain-size data. Based on these ages, the Matuyama and Brunhes boundary (MBB, ∼0.78 Ma) is deduced in L8 as inferred from the declination sequence. The bottom age of the loess-paleosol sequence extrapolated from the sedimentation rate is 2.13 Ma. The chronological sequence is therefore established. Several environmental indexes were changed coordinately in broad areas based on the chronological framework, indicating that it is logical and reliable.